Anticoagulation management: An interdisciplinary curriculum for family medicine residents - Nijjar, Jaspreet; Marr, Patricia; Toubassi, Diana; Kwan, Debora; Papoushek, Christine (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2023)
Implication Statement Anticoagulants are high-risk medications with the potential to cause significant patient harm if inappropriately managed. Medical trainees and practicing physicians often report inadequate education and uncertainty in decision-making related to anticoagulation therapy. To address this gap, an interdisciplinary Anticoagulation Management Training Program was developed for family medicine residents at the Toronto Western Family Health Team. Evaluation data demonstrated both improved knowledge and confidence in prescribing, monitoring, and adjusting anticoagulation therapy. This suggests that similar dedicated curricula be considered in other family medicine programs in order to optimize patient safety by enhancing the knowledge and self-efficacy of future practising physicians.